2001
DOI: 10.1136/jnnp.70.6.739
|View full text |Cite
|
Sign up to set email alerts
|

Anosmia in dementia is associated with Lewy bodies rather than Alzheimer's pathology

Abstract: Consensus clinical criteria for dementia with Lewy bodies had a sensitivity of 64% and specificity of 89%. In the absence of definite Alzheimer's disease, the criteria had sensitivity of 100%. In patients with definite Alzheimer's disease, anosmia was slightly more sensitive (55%) than the consensus criteria (33%). However, the addition of anosmia to the consensus criteria did not improve their overall performance. Conclusion-Dementia with Lewy bodies is associated with impaired odour detection. Misdiagnosis m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(87 citation statements)
references
References 37 publications
5
80
2
Order By: Relevance
“…While olfactory dysfunction has been demonstrated in AD, patients with Lewy body dementia have even greater impairments in olfaction, lending significance to the role of Lewy pathology in olfactory dysfunction [42][43][44] . Based on this assumption, it would be expected that nondegenerative causes of parkinsonism have intact olfaction, as is the case in vascular parkinsonism [45] and MPTP-induced parkinsonism [46] .…”
Section: Olfactory Loss As a Biomarker Of Pdmentioning
confidence: 99%
“…While olfactory dysfunction has been demonstrated in AD, patients with Lewy body dementia have even greater impairments in olfaction, lending significance to the role of Lewy pathology in olfactory dysfunction [42][43][44] . Based on this assumption, it would be expected that nondegenerative causes of parkinsonism have intact olfaction, as is the case in vascular parkinsonism [45] and MPTP-induced parkinsonism [46] .…”
Section: Olfactory Loss As a Biomarker Of Pdmentioning
confidence: 99%
“…Cross-sectional studies have clearly shown that hyposmia is a highly sensitive finding in PD, but it is not specific. Olfaction is also impaired in dementia with Lewy bodies (DLB) [11,12], pure autonomic failure [13], and amyotrophic lateral sclerosis, with mixed results found for Alzheimer's disease and multiple system atrophy [11,12]. Therefore, this nonmotor finding may be used as a premotor test to identify an at-risk group for PD, but it is certainly not diagnostic.…”
Section: Olfactionmentioning
confidence: 99%
“…In dementia patients, neuropathologic studies reported neuronal alterations in several subcortical structures such as the olfactory tract/bulb, anterior olfactory nucleus, orbito-frontal cortex, hippocampus, and amygdala in the olfactory system (Hubbard et al, 2007). Olfactory abnormalities have been reported in Alzheimer's disease (AD), but anosmia appears to be common in dementia with Lewy bodies (DLB) but not in pure AD (McShane et al, 2001). A Lewy body variant of AD had an increased frequency of anosmia compared with "pure" AD (Olichney et al, 2005).…”
Section: Olfactory Dysfunctionmentioning
confidence: 99%